2017
DOI: 10.3855/jidc.7800
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses and histopathological changes in a mouse model of Staphylococcus aureus-induced bloodstream infections

Abstract: Introduction: Staphylococcus aureus-induced bloodstream infections (BSIs) remain a prevalent clinical challenge and the underlying pathogenesis is still poorly understood. The aim of this study was to investigate the inflammatory responses and histopathological changes in BSIs in mice. Methodology: Male C57BL/6 mice were inoculated with S. aureus intravenously to induce BSIs. The survival rate, weight loss, and murine sepsis scores (MSS) were monitored in BSI and phosphate-buffered saline (PBS) control mice. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…Weight loss was significantly higher in the D and E treatment groups than in Groups B and F (unpublished data). This is in accordance with the research [8], which showed that rats induced by S. aureus bacteria concentrations of 4.5×10 4 -4.5×10 9 CFU/mL showed no weight loss. According to the research conducted by Reis et al .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Weight loss was significantly higher in the D and E treatment groups than in Groups B and F (unpublished data). This is in accordance with the research [8], which showed that rats induced by S. aureus bacteria concentrations of 4.5×10 4 -4.5×10 9 CFU/mL showed no weight loss. According to the research conducted by Reis et al .…”
Section: Resultssupporting
confidence: 93%
“…The results of this study are different from those conducted by Wu et al . [8] which showed rat died after being induced with S. aureus with successive concentrations ranging from 4.5×10 7 to 4.5×10 9 CFU/mL intravenously which were observed 7 days post-infection. Death in diabetic rats is due to the impaired immune system through decreased production and function of inflammatory cytokines, loss of phagocytic function, and body antioxidant production [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations